2006
DOI: 10.1128/jcm.00773-06
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Candidemia in Brazil: a Nationwide Sentinel Surveillance of Candidemia in Eleven Medical Centers

Abstract: Candidemia studies have documented geographic differences in rates and epidemiology, underscoring the need for surveillance to monitor trends. We conducted prospective candidemia surveillance in Brazil to assess the incidence, species distribution, frequency of antifungal resistance, and risk factors for fluconazole-resistant Candida species. Prospective laboratory-based surveillance was conducted from March 2003 to December 2004 in 11 medical centers located in 9 major Brazilian cities. A case of candidemia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
330
8
97

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(465 citation statements)
references
References 59 publications
30
330
8
97
Order By: Relevance
“…Nessa casuística, as espécies não-albicans foram mais freqüentes que Candida albicans, e destas, Candida parapsilosis (nº=7) foi a mais encontrada, seguida da Candida tropicalis (nº=5). Apesar dos números pequenos, e do caráter unicêntrico deste estudo, os dados encontrados estão de acordo com o estudo epidemiológico brasileiro que demonstrou que Candida albicans, Candida parapsilosis e Candida tropicalis causam a maioria das candidemias 9 . Embora tenha sido observada uma maior proporção de candidemia por Candida glabrata (9%) comparado com os dados brasileiros 9 , o número pequeno da candidemias não permite uma conclusão definitiva.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Nessa casuística, as espécies não-albicans foram mais freqüentes que Candida albicans, e destas, Candida parapsilosis (nº=7) foi a mais encontrada, seguida da Candida tropicalis (nº=5). Apesar dos números pequenos, e do caráter unicêntrico deste estudo, os dados encontrados estão de acordo com o estudo epidemiológico brasileiro que demonstrou que Candida albicans, Candida parapsilosis e Candida tropicalis causam a maioria das candidemias 9 . Embora tenha sido observada uma maior proporção de candidemia por Candida glabrata (9%) comparado com os dados brasileiros 9 , o número pequeno da candidemias não permite uma conclusão definitiva.…”
Section: Discussionunclassified
“…Apesar dos números pequenos, e do caráter unicêntrico deste estudo, os dados encontrados estão de acordo com o estudo epidemiológico brasileiro que demonstrou que Candida albicans, Candida parapsilosis e Candida tropicalis causam a maioria das candidemias 9 . Embora tenha sido observada uma maior proporção de candidemia por Candida glabrata (9%) comparado com os dados brasileiros 9 , o número pequeno da candidemias não permite uma conclusão definitiva. A epidemiologia de candidemia em centros do Nordeste brasileiro não é ainda muito conhecida 5 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It is particularly important in dialysis to prevent the formation of biofilm, because the reduced availability of nutrients and accumulation of toxic waste encourages the dispersal of cells, i.e., the release of cells from the original biofilm community to generate new communities in new places (Uppuluri et al 2010). Dispersed cells of Candida are responsible for candidemia and invasive disseminated candidiasis, which are among the most serious forms of infection and lead to the highest mortality rates (Colombo et al 2006, Bruder-Nascimento et al 2010. Isolates with MBIC n-folds higher than the MIC n (%) a: MIC amphotericin B = 2 µg/mL (Clinical and Laboratory Standards Institute M27-A3 document) (Guinea et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, which compared the clinical use of drugs such as fluconazole (FLC) and amphotericin B (AMB) showed that FLC is the best therapy in the empiric treatment of fungal infections due to lower toxicity and low cost (Pfaller et al 2003, Colombo et al 2006, Nucci et al 2010.…”
mentioning
confidence: 99%